2004
DOI: 10.1016/s1010-6030(03)00381-2
|View full text |Cite
|
Sign up to set email alerts
|

1,8-Naphthalimides for non-doping OLEDs: the tunable emission color from blue, green to red

Abstract: Substitution at the 4-position of 1,8-naphthalimide with electron-donating groups can increase fluorescent quantum yields and change emissive wavelengths from blue to red. Based on this molecular design concept, novel naphthalimide derivatives containing Schiff base moiety were prepared by condensing 4-hydrazino-1,8-naphthalimides with the aldehydes. Amino conjugation between the 4-amino-1,8-naphthalimide and the substituted moiety resulted in red shift of the absorption and fluorescence maximum wavelengths in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 54 publications
1
44
0
2
Order By: Relevance
“…Because the 1,8-naphthalimide fluorophore offers the possibility of long-wavelength emission, and recently it has been reported that addition of a 4-amino group can significantly change the fluorescent properties of the 1,8-naphthalimide fluorophore, [59][60][61][62][63] we were interested in using 4-amino-1,8-naphthalimide as a template for the design of long-wavelength fluorescent boronic acid reporter compounds. One way to induce the desired fluorescent property changes to such a template is to build in a mechanism in which binding of a sugar would perturb the fluorophore's electronic environment.…”
Section: The Designmentioning
confidence: 99%
“…Because the 1,8-naphthalimide fluorophore offers the possibility of long-wavelength emission, and recently it has been reported that addition of a 4-amino group can significantly change the fluorescent properties of the 1,8-naphthalimide fluorophore, [59][60][61][62][63] we were interested in using 4-amino-1,8-naphthalimide as a template for the design of long-wavelength fluorescent boronic acid reporter compounds. One way to induce the desired fluorescent property changes to such a template is to build in a mechanism in which binding of a sugar would perturb the fluorophore's electronic environment.…”
Section: The Designmentioning
confidence: 99%
“…[36] Long-wavelength emission has been observed with the 1,8-naphthalimide fluorophore, and the addition of a 4-amino group to this compound has been shown to significantly change its fluorescence properties. [12,[37][38][39] In our recent work, 4-amino-1,8-naphthalimide was used as a template for a series of long-wavelength fluorescent boronic acid reporters that showed fluorescence intensity increases upon sugar binding. [13] Somewhat related work was also reported by Trupp and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PF was chosen as the blue-lightemitting polymer, and 1,8-naphthalimide derivatives were chosen as the orange-light-emitting components, owing to their high photoluminescence (PL) quantum yields, tunable emission colors, and their ability to be attached to the polymer main and side chains. [30][31][32] For example, Ego et al reported that the emission color of fluorene-based polymers can be easily tuned across the whole visible range of the electromagnetic spectrum by incorporating perylene bisimide units in the main chain, as side chains, and at the chain termini. [32] The amount of 1,8-naphthalimide derivative in the resulting polymers was maintained in the 0.05-1.0 mol-% range in order to balance the relative intensity of the blue-light emission from PF with orange-light emission from a1,8-naphthalimide derivative unit.…”
Section: Resultsmentioning
confidence: 99%